Flash joule heating synthesis of porous graphene oxide from banana leaf waste for high-performance supercapacitor electrodes - Ikhwanul Qiram; Dewi Sartika; Wisnu Kuncoro; Willy Satrio Nugroho; Abdul Mudjib Sulaiman Wahid (Mechanical Engineering for Society and Industry, 2026)
This study investigates the synthesis of porous graphene oxide (GO) derived from banana leaf waste using the Flash Joule Heating (FJH) method for supercapacitor electrode applications. Carbonization was conducted at input voltages of 5, 10, and 15 VA for 2 s, followed by activation with 0.3 M KOH. Structural characterization (SEM, EDX, FTIR, and XRD) confirmed the formation of hierarchical porous carbon with oxygen-containing functional groups. Electrochemical evaluation revealed that the sample synthesized at 10 VA exhibited the best performance, achieving a specific capacitance of 345 F g⁻¹, low internal resistance of 0.65 Ω, and capacitance retention of 95% after 500 cycles. In contrast, the 5 VA sample showed lower conductivity due to its amorphous structure, while the 15 VA sample exhibited reduced capacitance due to excessive macropore formation. These results demonstrate that controlled FJH voltage plays a critical role in optimizing pore structure and electrochemical performance, highlighting banana leaf-derived GO as a promising and sustainable electrode material for high-performance supercapacitors.